Visceral Adiposity and Risk of Stroke: A Mendelian Randomization Study - Xu, Ran; Hu, Xinzhi; Wang, Tao; Yang, Yutong; Jiang, Nan; Luo, Jichang; Zhang, Xiao; Patel, Aman B.; Dmytriw, Adam A.; Jiao, Liqun (Frontiers in Neurology, 2022)
Purpose In recent years, metabolic syndrome has risen in prevalence and brought a heavy disease burden to modern society. As the representative aspect of metabolic syndrome, obesity has been shown to be related to an increased risk of stroke. Given that visceral adipose tissue (VAT) forms the fundamental basis of central obesity, we sought to explore a causal relationship between VAT and stroke by using mendelian randomization (MR) methods. Methods Based on two large genome-wide association studies (GWAS) including 325,153 and 35,762 cases of VAT and stroke respectively, we conducted a MR study which has the inherent advantage of reducing the noise of confounding and reverse causation. Results VAT had a significant causal association with ischemic stroke (OR, per 1kg increase in VAT mass, 1.30; 95% CI, 1.18 1.45; P = 5.87E-07) as opposed to hemorrhagic stroke (OR, 1.15; 95% CI, 0.70 1.88, P = 5.81E-01) as evaluated with inverse-variance weighting (IVW). Regarding subtypes of ischemic stroke, there was a significant causal effect for cardioembolic stroke (OR, 1.34; 95% CI, 1.13 1.58, P = 8.07E-04), and potential causal effect for small-vessel stroke (OR, 1.32; 95% CI, 1.06 1.65, P = 1.39E-02) and large-artery atherosclerotic stroke (OR, 1.33; 95% CI, 1.03 1.70, P = 2.59E-02). Conclusions This study provides potential evidence for a causal role of VAT in ischemic stroke and could suggest novel genetical therapeutic strategies for distinct subtypes of ischemic stroke.